Implementation of Inpatient Electronic Consultations During the COVID-19 Crisis and Its Sustainability Beyond the Pandemic: Quality Improvement Study - Anna S Aledia; Amish A Dangodara; Aanya A Amin; Alpesh N Amin (JMIR Publications, 2024)
BackgroundLimiting in-person contact was a key strategy for controlling the spread of the highly infectious novel coronavirus (COVID-19). To protect patients and staff from the risk of infection while providing continued access to necessary health care services, we implemented a new electronic consultation (e-consult) service that allowed referring providers to receive subspecialty consultations for patients who are hospitalized and do not require in-person evaluation by the specialist. ObjectiveWe aimed to assess the impact of implementing e-consults in the inpatient setting to reduce avoidable face-to-face referrals during the COVID-19 pandemic. MethodsThis quality improvement study evaluated all inpatient e-consults ordered from July 2020 to December 2022 at the University of California Irvine Medical Center. The impact of e-consults was assessed by evaluating use (eg, number of e-consults ordered), e-consult response times, and outcome of the e-consult requests (eg, resolved electronically or converted to the in-person evaluation of patient). ResultsThere were 1543 inpatient e-consults ordered across 11 participating specialties. A total of 53.5% (n=826) of requests were addressed electronically, without the need for a formal in-person evaluation of the patient. The median time between ordering an e-consult and a specialist documenting recommendations in an e-consult note was 3.7 (IQR 1.3-8.2) hours across all specialties, contrasted with 7.3 (IQR 3.6-22.0) hours when converted to an in-person consult (P<.001). The monthly volume of e-consult requests increased, coinciding with surges of COVID-19 cases in California. After the peaks of the COVID-19 crisis subsided, the use of inpatient e-consults persisted at a rate well above the precrisis levels. ConclusionsAn inpatient e-consult service was successfully implemented, resulting in fewer unnecessary face-to-face consultations and significant reductions in the response times for consults requested on patients who are hospitalized and do not require an in-person evaluation. Thus, e-consults provided timely, efficient delivery of inpatient consultation services for appropriate problems while minimizing the risk of direct transmission of the COVID-19 virus between health care providers and patients. The service also demonstrated its value as a tool for effective inpatient care coordination beyond the peaks of the pandemic leading to the sustainability of service and value.